MANAJEMEN PEMBIAYAAN PENDIDIKAN UNTUK MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH ALIYAH AL-MANAR KECAMATAN MEDAN JOHOR - Mesiono Mesiono; M Fajri Syahroni Siregar; Imron Bima Saputra (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
An optimal madrasah education cannot be separated from professional management, it can happen which is supported by available funding sources. Education that is not financed will not work. Madrasah Aliyah Al-Manar Medan Johor has a source of funds from the community for the implementation of the learning process. This research discusses the management of Madrasah financing including planning, implementation and supervision of financing. This type of research uses descriptive qualitative methods, while the data analysis techniques use observation, interview and documentation techniques.